Penanganan Sampah Rumah Tangga di Dusun Petoyan, Desa Giritirto, Kecamatan Purwosari, Kabupaten Gunungkidul - Dyah Suryani; Iin Rosita Anggraini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The waste problem has social, environmental, and health impacts. This community service aims to handle household waste in Petoyan Hamlet, Giritirto Village, Purwosari District, Gunung Kidul Regency, Yogyakarta. The method of this activity is community diagnosis, village community consultation (MMD), and conducting solutions/interventions with the community. This activity shows that most of the problems found are the management of household waste by the community is burned and buried. Then from the pre-test and post-test results, it was found that some people still do not understand the difference between organic and inorganic waste. Interventions carried out in this activity were the distribution of leaflets and outreach conducted door to door. It is hoped that the local government can provide a waste disposal site (TPS) and a final disposal site (TPA).